Potensi Tumbuhan Jamblang (Syzygium cumini (L) Skeels) Sebagai Antipiretik Berdasarkan Kandungan Senyawa Aktif: Lterature Review Article - Anita Fajriyani; Icha Nurfirzatulloh; Nabilla Putri Nurizha; Satrio Adiputra; Himyatul Hidayah (Peneliti.net, 2023)
Jamblang (Syzygium cumini (L.) Skeels) is a family of myrtaceae, this plant can be used for medicinal purposes. This study aims to determine the active compound content of the jamun plant (Syzygium cumini (L.) Skeels) as an antipyretic. The method used in this study is the Literature Review Article (LRA) method by searching databases taken from various scientific articles through Google Scholar, Science Direct, PubMed. Based on a review of several studies of the jamun plant (Syzygium cumini (L.) Skeels) has antipyretic pharmacological activity in fruit parts, dry seeds and leaves.